A Review on the Methods of Interlaminar Properties Using Nanomaterials to Reinforce Carbon Fiber Epoxy Composites. (September 2020) - Xu, Jingli; Liu, Aiyun; Jia, Huamin; Liu, Fangbiao; Zhang, Jianqin; Guo, Jianfen; Wei, Huazhen; Zhang, Haiyun; Wang, Danyong; Li, Shuhu
Abstract: Carbon fiber reinforced epoxy composites is playing a role in reducing structural weight and costs, saving resources and optimizing processes. However, the low properties of epoxy matrix and the weak interfacial bonding between carbon fiber and epoxy lead to the poor interlaminar performancec for carbon fiber or fabric reinforced epoxy composites. The application of nanomaterials is an effective way to improve or enhance the interlaminar properties of composite materials. Therefore, this paper summarized the research on the methods of nanomaterialsto reinforce resin matrix, and nanomaterials-carbon fibers multi-scale reinforcement to enhance the interlaminar performace, and nanomaterials to distribute the surface of prepreg uniformly, and nanomaterials to promote interfacial binding energy between carbon fiber and epoxy and nanomaterials macrostructure to improve the interlaminar properties of composites.